2017
DOI: 10.21565/ozelegitimdergisi.283374
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Kaynaştırmaya İlişkin Görüşlerinin Belirlenmesi

Abstract: The general purpose of this study was to determine the opinions of preschool teachers about inclusion. Participants were 45 preschool teachers from 8 preschools who had students with special educational needs in their classes during the study or had in the previous years and who were working in public preschools in Eskisehir, Turkey. They had 2-27 years of teaching experience. Semi-structured interviews were conducted with the teachers and the data were analyzed descriptively. The results of the study revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…This may refer to the lack of awareness or responsibility on IEP, the inadequacy of the Special Education course they take in terms of developing and implementing IEP or the perception of the IEP development process as difficult. Previous studies that included Classroom Education and branch teachers revealed that teachers considered themselves insufficient both for inclusive practices and IEP preparation and implementation processes (Babaoğlan & Yılmaz, 2010;Batu et al, 2017;Çuhadar, 2006;Demirezen & Akhan, 2016;Öztürk & Eratay, 2010). Effective and efficient use of the resources to increase the quality is at the forefront of accountability in education (Hammond, Wilhoit, & Pittenger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This may refer to the lack of awareness or responsibility on IEP, the inadequacy of the Special Education course they take in terms of developing and implementing IEP or the perception of the IEP development process as difficult. Previous studies that included Classroom Education and branch teachers revealed that teachers considered themselves insufficient both for inclusive practices and IEP preparation and implementation processes (Babaoğlan & Yılmaz, 2010;Batu et al, 2017;Çuhadar, 2006;Demirezen & Akhan, 2016;Öztürk & Eratay, 2010). Effective and efficient use of the resources to increase the quality is at the forefront of accountability in education (Hammond, Wilhoit, & Pittenger, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed that male teachers and teacher candidates have more positive attitudes towards inclusive education than female counterparts; and that teachers/teacher candidates who took courses focused on inclusive or special education were more positive about including children with special needs (Dalğar, 2011;Şahbaz and Kalay, 2010). It is also found that preschool teachers need knowledge and skills in relation to teaching children with special needs, classroom management, working with families of children with special needs, evaluation and instruction in natural environments, individualized education programs (e.g., Batu et al, 2017;Gezer, 2017;Gök and Erbaş, 2011;Özaydın and Çolak, 2011;.…”
Section: Extended Summarymentioning
confidence: 99%
“…Alan yazında kaynaştırma uygulamalarında yaşanan sorunlara dair pek çok bulgu yer almaktadır (Sadioğlu, Bilgin, Batu, & Oksal, 2013;Denizli & Uzoğlu, 2016;Erişkin, Kıraç, & Ertuğrul, 2012;Saraç & Çolak, 2012;Yılmaz & Batu, 2016). Bu bulgulardan öne çıkanlar; öğretmen tutumlarındaki olumsuzluklar (Demir & Açar, 2011;Engin, Tösten, Kaya, & Köselioğlu, 2014;Sadioğlu, Batu, & Bilgin, 2012;Saloviita, 2020;Sharma, Aiello, Pace, Round, & Subban, 2018;Yatgın, Sevgi, & Uysal, 2015), öğretmenlerin yeterlilik sorunları (Akalın, 2015;Eldeniz-Çetin & Acay-Sözbir, 2016;Jez & Luneta, 2018;Kot, Sönmez, Yıkmış, & Çiftçi-Tekinarslan, 2015;Love & Horn, 2021;Vural & Yıkmış, 2008), okul öncesi kaynaştırma uygulamalarına yönelik sorunlar (Batu, Odluyurt, Alagözoğlu, Çattık, & Şahin, 2017;Sığırtmaç Dikici, Hoş, & Abbak, 2011;Tuş & Çifçi Tekinarslan, 2013), fiziki mekana, sınıf mevcutlarına dair sorunlar (Kurt, 2015;Nayır & Karaman-Kepenekci, 2013;Akay, Uzuner, & Girgin, 2014;Ünal, 2008), diğer öğrenciler ve ailelerinin olumsuz tutumlarıdır (Ayral & diğ., 2015;Bakkaloğlu, Özbek, & Sucuoğlu, 2021;Turhan, 2007).…”
Section: Introductionunclassified